Fatherhood Experiences of Some Selected Young Adults in Bangladesh - Anisur Khan; Md. Riyajul Islam Nuhash (Journal of Child, Family, and Consumer Studies, 2025)
Fatherhood is a multidimensional and evolving concept, often shaped by cultural, emotional, and relational dynamics. In Bangladesh, scholarly exploration of fatherhood remains significantly limited, making it difficult to establish a prototypical understanding or to trace its changing meanings. This study aims to explore the lived experiences and interpretations of fatherhood among educated, motherless young adults, focusing specifically on their emotional attachment to their surviving fathers. Drawing on qualitative interviews with 10 young adults, this study identifies four key themes: eternal maternal bondage, grief and adjustment mechanisms, the role and involvement of fathers, and the extent of family support to fathers. These themes reflect how participants make sense of fatherhood through their personal journeys. These young adults continue to share a strong bond with their surviving mothers, but have closely observed how their fathers coped with grief and bereavement following the loss of their partners, how they assumed parenting roles and responsibilities in raising them, and the extent to which family and relatives supported their fathers during this period. The insights provided by this study contribute to a nuanced understanding of fatherhood in Bangladesh and offer valuable implications for both theoretical frameworks and policy development concerning family dynamics and parental roles.